THU0558 ANTI-CCP NEGATIVE PATIENTS WITH NEW MUSCULOSKELETAL SYMPTOMS: IMPROVING REFERRALS FROM PRIMARY CARE. (2nd June 2020) - Garcia-Montoya, L.; Nam, J.; Mankia, K.; Duquenne, L.; DI Matteo, A.; Emery, P.
Abstract : Background: The presence of anti-cyclic citrullinated peptide antibodies (anti-CCP antibodies) is associated with progression to inflammatory arthritis (IA) [1]; however, most patients attending primary care with a new non-specific musculoskeletal (MSK) complaint and no clinical synovitis have a negative result for this test (CCP-). Considering that only a small proportion of these individuals will be diagnosed with an IA within the next 12 months, predicting disease progression in these patients appears to be more challenging. Objectives: To investigate factors that could be associated with disease progression in patients testing CCP- in order to optimise primary care referrals to Rheumatology. Methods: A prospective observational study recruiting patients over 16 years old with a new MSK complaint and no clinical synovitis was conducted. Patients recruited from primary care centres across the UK from July 2007 until November 2018 were included in this analysis. Those testing negative for the anti-CCP2 assay (initially phadia, later bioplex) were sent questionnaires 1 year later, and GPs were contacted in November 2019 to confirm their disease status. Results: 7521 eligible patients were recruited from primary care. 7290 (97%) of them were CCP- and 5678 returned the questionnaire after 1 year. 239 patients (4.2%) of these CCP- reported progression to IA; however, this diagnosis was only confirmed in 53 of them (0.93%). In another 38 patients, the IA diagnosis could not be confirmed and therefore they were not included in the analysis. 21 patients progressed to rheumatoid arthritis (RA), 13 to spondyloarthritis, 11 to polymyalgia rheumatica (requiring disease-modifying anti-rheumatic drugs), 3 to polymyositis, 3 to systemic lupus erythematosus and 2 to systemic sclerosis. Table 1 describes the most troublesome joints and table 2 other concomitant MSK diagnoses of the non-progressors/ progressors; and among the last ones, the RA group. Multivariable analysis showed that pain in specific joints was associated with development of IA within the following 12 months: hand odds ratio (OR) 2.1 [95%CI (1.09-4.16), p=0.027], knee OR 2.0 [95%CI (1.13-3.91), p=0.02], and shoulder OR 1.8 [95%CI (1.02-3.45), p=0.043). Smoking exposure, having a first degree relative with RA and gender were not predictive for progression. Older age showed only a slightly higher risk for IA [OR 1.04, 95%CI (1.01-1.06) p=0.001]. Conclusion: In CCP- patients without clinical synovitis, hand, knee and shoulder pain should be investigated more carefully as these involve a higher risk of progression to IA. Patient reported outcomes regarding rheumatic diseases are not reliable; the distribution of joint pain seems to be a more useful tool than the family history when assessing the need for referral to Rheumatology. References: [1]Rakieh C. Ann Rheum Dis. 2015;74:1659-66 Acknowledgments: National Institute of Health Research (NIHR) Leeds Biomedical Research Centre (BRC) Disclosure of Interests: Leticia Garcia-Montoya: None declared, Jacqueline Nam: None declared, Kulveer Mankia: None declared, Laurence Duquenne: None declared, Andrea Di Matteo Grant/research support from: the publication was conducted while Dr. Di Matteo was an ARTICULUM fellow, Paul Emery Grant/research support from: AbbVie, Bristol-Myers Squibb, Merck Sharp & Dohme, Pfizer, Roche (all paid to employer), Consultant of: AbbVie (consultant, clinical trials, advisor), Bristol-Myers Squibb (consultant, clinical trials, advisor), Lilly (clinical trials, advisor), Merck Sharp & Dohme (consultant, clinical trials, advisor), Novartis (consultant, clinical trials, advisor), Pfizer (consultant, clinical trials, advisor), Roche (consultant, clinical trials, advisor), Samsung (clinical trials, advisor), Sandoz (clinical trials, advisor), UCB (consultant, clinical trials, advisor)